1989
DOI: 10.1002/anr.1780321019
|View full text |Cite
|
Sign up to set email alerts
|

Isotype analysis of the anti–CENP‐B anticentromere autoantibody: Evidence for restricted clonality

Abstract: Utilizing the centromere B fusion protein (CENP-B) and specific, matched monoclonal antiisotype reagents in an enzyme-linked immunosorbent assay, we found that anti-CENP-B autoantibodies were skewed to the IgGl isotype. The overall K : A light chain ratio was 2: I, although several individual sera showed a strong predominance of one of the light chains. Isoelectric focusing of light chain-skewed sera showed polyclonal patterns. Our findings are consistent with the anti-CENP-B autoantibody response being a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Both above mechanisms may be operational in generating scleroderma autoantibodies. We have found evidence that both play a role in the origin of scleroderma autoantibodies [32,33,[41][42][43]. We hypothesize that the scleroderma autoantibodies share a 'specific scleroderma' V H -Id.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Both above mechanisms may be operational in generating scleroderma autoantibodies. We have found evidence that both play a role in the origin of scleroderma autoantibodies [32,33,[41][42][43]. We hypothesize that the scleroderma autoantibodies share a 'specific scleroderma' V H -Id.…”
Section: Introductionmentioning
confidence: 85%
“…In scleroderma we have reported a germ-line gene configuration for an IgM antitopoisomerase-I [41], and evidence of oligoclonality in the anti-CENP-B autoantibodies [42].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have not succeeded in narrowing down epitope I under 65 amino acids. Given our observation that IgM-or IgA-class autoantibodies of the longitudinal sera in this study were not found, but that strong IgG-class responses persisted for years along with the restricted clonality in anti-CENP-B response characterized by Eisenberg et al (26), T cells are probably important for their production and immunoregulation.…”
Section: Discussionmentioning
confidence: 40%
“…As noted in early studies, CENP-B is an unlikely candidate for selfimmunization due to centromeres accounting for a small portion of the intracellular volume [37]. Regardless, detailed study of the ACA serotype has characterized it as a product of an antigen-driven response resulting in high titers [9,20,45].…”
Section: Autoantibodies Targeting Cenp-b Define Acasmentioning
confidence: 99%